α - Robert Faff (Journal of Accounting and Management Information Systems (JAMIS), 2014)
"Alpha" has symbolic importance on the investments side of finance. That is, a fundamental pillar of modern finance theory is the risk-return relation, and traditionally alpha is taken to represent the degree of "mispricing" in asset returns. But, such an interpretation is not always appropriate – seemingly paradoxically, for certain specific setups alpha embodies pricing information. In this paper, I explain and illustrate the distinguishing circumstances between these two diametrically opposed cases.
Keywords: G12; 650; Alpha; Beta; empirical asset pricing; mispricing information; pricing information